BEACH HYDROLOGY: IMPLICATIONS FOR BEACH QUALITY ALONG SOUTHERN GEORGIAN BAY, CANADA - Spina, Natalie E. (My University, 2011)
Recreational beaches of the Great Lakes play a critical role in the quality of life for beach goers and contribute to the economic and environmental health of the Great Lakes region. Over the past decade, concerned local residents, municipalities, and public beach goers have observed the deteriorating beach quality along the shores of the Great Lakes. Numerous problems exist at these beaches including: high levels of E.coli, encroachment of invasive and non-native vegetation, iron staining, loss of sand. However, the more pervasive problem appears to be increased wet conditions at beaches that use to be dry. This study was undertaken to investigate the physical and hydrological factors that control wet and dry beaches, in order to determine why these beaches exist. Combined field, laboratory, and modelling methodologies were used to characterize four beach sites and calibrate beach models along southern Georgian Bay in Tiny Township, ON. The results of this research indicate that there are three interconnected factors that influence wet and dry beaches, including: (1) texture of a beach, (2) depth to the water table, and (3) elevation of the ground surface. Texture is the primary factor that controls the moisture conditions at a beach even though all beaches were classified as sands. This is a consequence of the fact that fine grained sands have significantly higher capillary rise and retain higher moisture contents above the water table compared to coarse grained sands. Depth to the water table influences the moisture conditions at a beach through its association with the relative position of the top of the capillary rise within respect to the surface of the beach. Ground surface elevation influences the depth of sand above the water table at a beach; lower and flatter surface elevations have the water table (and capillary rise) closer to the beach surface than at beaches with steeper elevations. In summary, wet beaches have high moisture contents at and near the surface of a beach (> 10 %), shallow water tables (~ < 50 cm), and flat ground surface elevations. Dry beaches have low moisture contents at and near the surface of a beach (< 10 %), deep water tables (~ > 50 cm), and steep ground surface elevations. Using the numerical model HYDRUS-2D, four calibrated beach models provide a framework for beach managers to gain insights into beach quality issues through scenario testing. Beaches with shallow water tables and flat surface elevations (either natural or human-induced) are at greater risk of becoming wet under high lake level scenarios than beaches with steeper surfaces (dry beaches). Heavy precipitation events are temporary and do not convert dry beaches into wet beaches and high evaporation rates do not convert wet beaches into dry beaches; conversion of beaches is mainly influenced by beach surface alterations (e.g. bulldozing and removing sand dunes). The conclusion of this study is that hydrological factors are primary controls on the quality of the beaches and the associated problems along the shores of the Great Lakes.
Keywords: hydrology; sand texture; Great Lakes; beaches; beach management; numerical modelling; Hydrology; Hydrology